An Interactive Web-Based Learning Tool for the Study of Blood Flow in a Coronary Artery System - Thongnak, S.; Wiwatanapataphee, B.; Wu, Yong Hong (Pushpa Publishing House, 2011)
In this paper, we present a Web-Based learning tool for undergraduate mathematics students. The tool is developed using Moodle for students to learn the principal theories of fluid dynamics and its application to the study of blood flow in the coronary artery system. The tool consists of the web-based interactive course materials with exercises, discussion forum, relevant databases, and other Moodle facilities. A learning effectiveness investigation shows that the developed WBL tool significantly improves students' learning outcomes.